On Maintaining and Blurring Gender Differentiation: An Analysis of the Polish Media Discourse on Iga Świątek and Robert Lewandowski - Krzysztof Arcimowicz (Studia z Teorii Wychowania, 2025)
Iga Świątek and Robert Lewandowski are two of the most popular athletes in Poland. They are icons of contemporary culture, capable of influencing social norms, values and aspirations, especially among young people. The main objective of the article is to analyse the discursive strategies related to the maintaining and blurring of gender differentiation in Polish media discourse on the professional sphere of Świątek and Lewandowski. The primary theoretical perspective of the research is the theory of hegemonic masculinity. The research material includes 458 selections from Internet and television coverage published between 2018 and 2024. This paper presents the results of a critical discourse analysis, in which the tools of the discourse-historical approach and quantitative content analysis were used. The discourse is not homogeneous becauseon the one hand it contains, strategies of gender differentiation connected with infantilisation and trivialisation of the tennis player and the evaluation of her external appearance, and on the other hand, there are numerous examples of metaphorisation and hyperbolisation of the athleticism of both Lewandowski and Świątek, related to the blurring of gender differences.